The Effect of Oral Vitamin D on Patients with Alopecia Areata - Ethar Salah Nadhim (Journal of Global Pharma Technology, 2019)
Background: Patients who had alopecia areata (AA) presented with markedly lower levels of vitamin D3. Adding to that, vitamin D supplementation could have a protective role in human autoimmune illnesses such as AA, so the aim of the study was to identify the role of systemic vitamin D effect on patients with AA in comparison with the other medications, study the effect of combination of vitamin D and other medications on all symptoms of AA and study the C-reactive protein (CRP) and its relationship with AA. Conclusion: The patients with AA who were treated by combination treatment (steroids and vitamin D) had a better response than the patients who were treated by steroids only, and the response of the group of patients with AA who were treated by vitamin D only was not significant. There was non-significant association between CRP and AA.Keywords: Vitamin D, Alopecia areata, Vitamin D deficiency.